The Relationship between Expertise in Sports, Visuospatial, and Basic Cognitive Skills - Heppe, Holger; Kohler, Axel; Fleddermann, Marie-Therese; Zentgraf, Karen (Frontiers in Psychology, 2016)
Team sports place high demands on visuospatial and other cognitive skills. However, there is a lack of research on visuospatial skills of elite athletes and there are heterogeneous results on basic cognitive skills of this population. Therefore, this series of studies tested different cognitive skills in elite team sports athletes. In Experiment 1, elite athletes were compared to recreational athletes, but no differences were observed between the groups in choice response time (CRT) and mental rotation (MR). To see if differences could be observed when the tested groups had a greater difference in expertise and more representative stimuli, in Experiment 2, we tested CRT and MR of elite athletes who had higher level of expertise, and we also used three-dimensional human stimuli. Overall, we still found no differences in MR; however, elite athletes did have shorter CRTs. In Experiment 3, instead of testing MR, we compared elite athletes’ and recreational athletes’ basic cognitive skills, such as processing speed, letter readout speed, memory span, and sustained attention. We found that elite athletes only performed better in sustained attention. Building on this data, in a supplementary analysis (Experiment 4) we tested whether MR and CRTs are correlated with basic cognitive skills. Results show that processing speed is the best predictor for MR, whereas letter readout speed explains most of the variance in CRTs. Finally, we discuss these findings against the backdrop of expertise and offer implications for future studies on mental rotation.